Do Unemployment Insurance Recipients Actively Seek Work? Evidence From Randomized Trials in Four U.S. States - Olivier Deschênes; David Ashmore; Orley C. Ashenfelter (Institute for the Study of Labor (IZA), 2000)
In this paper we report the results of the only field test of which we are aware that uses randomized trials to measure whether stricter enforcement and verification of work search behavior alone decreases unemployment claims and benefits paid in the U.S. unemployment insurance (UI) program. These experiments, which we implemented in four sites in Connecticut, Massachusetts, Virginia, and Tennessee, were designed to explicitly test claims based on nonexperimental data, summarized in Burgess and Kingston (1987), that a prime cause of overpayments is the failure of claimants to actively seek work. Our results provide no support for the view that the failure to actively search for work has been a cause of overpayments in the UI system.
Keywords: C93; J65; 330; Social experiment; overpayment; work-search requirement; Arbeitsuche; Arbeitsangebot; Arbeitslosenversicherung; Schätzung; Teilstaat; USA